ENZYME ESTIMATION BASED ON BACTERIAL INTERACTIONs WITH Pleurotus SPP. - Sharma, Shivani; Kaur, Samandeep; Sodhi, Harpreet Singh (Mushroom Research, 2020)
Lignocellulosic material is the most abundant renewable source composed of lignin, hemicelluloses and cellulose present on earth. Lignin acts as a physical barrier to underneath cellulose which can be used for the production of useful products. Some white rot fungi such as Pleurotus spp. has the capability of degradation due to the production of a plethora of ligninolytic enzymes. This degradation process can be improved by coculturing the Pleurotus spp. with lignin degrading bacterial spp. In this study, the coculturing of two bacterial spp. Bacillus and Delftia with Pleurotus spp. i.e. Pleurotus florida and Pleurotus sajor-caju was investigated. No antagonistic effect was observed in the interaction of the bacterial strains with fungal species. During ligninolytic enzyme production studies on Mushroom Minimal Media (MMM) containing paddy straw as an inducer, it was observed that enzyme production was more in media inoculated with bacterial species. Therefore, coculturing of the bacteriaÂ  with Pleurotus can enhance the digestibility of the paddy straw.